Natural history of osteonecrosis of the jaw in patients with multiple myeloma - Badros, A.; Terpos, E.; Katodritou, E.; Goloubeva, O.; Kastritis, E.; Verrou, E.; Zervas, K.; Baer, M.R.; Meiller, T.; Dimopoulos, M.A. (Journal of Clinical Oncology, 2008)
Purpose: To evaluate the natural history of bisphosphonate-related osteonecrosis of the jaw (ONJ) in patients with multiple myeloma. Patients and Methods: Ninety-seven patients with myeloma from the United States (n = 37) and Greece (n = 60) were observed prospectively for a minimum 3.2 years after ONJ. Patients characteristics were similar with regard to age, bisphosphonate use, and myeloma therapy, except more autologous transplantations were performed on patients in the United States than in Greece (73% v 28%; P < .0001). Results: ONJ resolved in 60 patients (62%), resolved and recurred in 12 patients (12%), and did not heal in 25 patients (26%). Dental procedures preceded ONJ in 46 patients (47%) and were more common in those with single episodes (35 of 60, 58%) than recurrent or nonhealing (11 of 37, 30%; P = .007). Recurrent ONJ followed reinitiation of bisphosphonates in six of 12 patients. Greek patients had more bone pain than United States patients (60% v 30%, P = .001) and were less likely to restart bisphosphonates (5% v 35%, P < .0002). Myeloma relapses were more common in patients with recurrent/nonhealing than single-episode ONJ (84% v 62%; P = .02). Median overall survival from myeloma diagnosis was 10.8 years (95% CI; 9.3 years to not reached) and did not differ between patients with single, recurrent, and nonhealing ONJ (P = .2). Conclusion: ONJ healed in 75% of patients. Patients with spontaneous ONJ have a higher risk of nonhealing and recurrence. Reinitiating bisphosphonates after healing of ONJ is a reasonable option in patients experiencing relapse who are at risk of skeletal complications. Further studies of the pathogenesis and healing of ONJ are needed. © 2008 by American Society of Clinical Oncology.